Pengaruh Produk Domestik Bruto, Pendidikan, dan Teknologi Terhadap Pengangguran di Negara Berkembang ASEAN - Dini Puspitasari (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Gross Domestic Product (GDP) per capita in percentage growth, education, and technology on unemployment rates in five developing ASEAN countries: Brunei Darussalam, Indonesia, Malaysia, Thailand, and the Philippines. GDP per capita is used as an indicator of economic growth, education is proxied by the average years of schooling, and technology is measured by the percentage of individuals with internet access. The study utilizes annual panel data from 2000 to 2023 and employs panel data regression analysis. The results show that GDP per capita (%) has a negative but statistically insignificant effect on unemployment, indicating that economic growth does not necessarily lead to a reduction in unemployment. Education has a positive and significant effect, suggesting a possible mismatch between educational outcomes and labor market demands. Meanwhile, technology has a negative and significant effect on unemployment, implying that increased access to information technology contributes to job creation, particularly through digital-based employment opportunities. These findings highlight the importance of integrated policy approaches in economic growth, education alignment, and technological development to effectively address unemployment issues across ASEAN developing countries.
Reaploud Repository February_Hasyim
Keywords: unemployment; GDP per capita (%); education; technology; ASEAN